2012
DOI: 10.5194/tcd-6-469-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the criticality of cracks in ice shelves using finite element simulations

Abstract: The ongoing disintegration of large ice shelf parts in Antarctica raise the need for a better understanding of the physical processes that trigger critical crack growth in ice shelves. Finite elements in combination with configurational forces facilitate the analysis of single surface fractures in ice under various boundary conditions and material parameters. The principles of linear elastic fracture mechanics are applied to show the strong influence of different depth dependent functions for the density and t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Our model does not simulate crack propagation, which as hypothesized in Weertman [, ], van der Veen [], Rist et al [], Plate et al [], and as observed in Fricker et al [], and Bassis et al [, , ] on the rifts of the Amery Ice Shelf, is controlled by the elastic stress regime at the rupture tip. However, propagation models for rifts and faults are preconditioned by the creep stress distribution, which is then applied as a load to the linear elastic stress regime near the rupture tip [ van der Veen , ; Larour et al , ; Hulbe et al , ; Plate et al , ]. As such, our model is well suited for this type of loading, as it takes into account the presence of cracks and the way they impact the background stress of the ice shelf.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our model does not simulate crack propagation, which as hypothesized in Weertman [, ], van der Veen [], Rist et al [], Plate et al [], and as observed in Fricker et al [], and Bassis et al [, , ] on the rifts of the Amery Ice Shelf, is controlled by the elastic stress regime at the rupture tip. However, propagation models for rifts and faults are preconditioned by the creep stress distribution, which is then applied as a load to the linear elastic stress regime near the rupture tip [ van der Veen , ; Larour et al , ; Hulbe et al , ; Plate et al , ]. As such, our model is well suited for this type of loading, as it takes into account the presence of cracks and the way they impact the background stress of the ice shelf.…”
Section: Discussionmentioning
confidence: 92%
“…As such, our model is well suited for this type of loading, as it takes into account the presence of cracks and the way they impact the background stress of the ice shelf. In models such as van der Veen [] or Plate et al [], the longitudinal stress applied to the rift flanks is taken equal to the background stress in which the crack is propagating. Such background stresses should therefore take into account the presence of the crack itself, which our model does.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field observations show that ductile fracture also occurs in ice shelf rifts, although it typically is associated with slower growth (Bassis et al, ). Linear elastic fracture mechanics is well suited to describe brittle fracture and has previously been used in the study of ice shelf rift propagation, crevasse growth, calving, and hydrofracture (Alley et al, ; Krawczynski et al, ; Krug et al, ; Larour et al, ; Nemat‐Nasser et al, ; Plate et al, ; Rist et al, ; Scambos et al, ; Smith, ; Van der Veen, ; Yu et al, ; Weertman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Field observations show that ductile fracture also occurs in ice shelf rifts, although it typically is associated with slower growth [Bassis et al, 2007]. Linear elastic fracture mechanics is well suited to describe brittle fracture and has previously been used in the study of ice shelf rift propagation, crevasse growth, calving, and hydrofracture [Weertman, 1971[Weertman, , 1973Smith, 1976;Nemat-Nasser et al, 1979;Van der Veen, 1998;Rist et al, 2002;Larour et al, 2004a;Alley et al, 2005;Krawczynski et al, 2009;Scambos et al, 2009a;Plate et al, 2012;Krug et al, 2014;Yu et al, 2017].…”
Section: Introductionmentioning
confidence: 99%